2022
DOI: 10.3389/fimmu.2022.1006395
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the STING signaling in COVID-19

Abstract: The coronavirus disease 2019 (COVID-19) pandemic caused by the infection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has cast a notorious damage to the public health and global economy. The Stimulator of Interferon Genes (STING) is a crucial element of the host antiviral pathway and plays a pivotal but complex role in the infection and development of COVID-19. Herein, we discussed the antagonistic mechanism of viral proteins to the STING pathway as well as its activation induced by host cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 88 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…As adjuvants, the STING agonist CF501 was combined with human IgG Fc-conjugated receptor binding domain (RBD) from the original SARS-CoV-2 strain, inducing highly potent and durable protective immunity responses without apparent biological toxicity. 123,186 As mentioned earlier, Mn 2+ NPs can enhance retention and cellular uptake, leading to prolonged activation of the cGAS-STING pathway after injection. Zhang et al 187 found that NP manganese was the most potent adjuvant in stimulating immune responses to SARS-CoV-2 protein-based subunit vaccines, as evidenced by the concentration of RBD-specific IgG and specific neutralizing antibodies of SARS-CoV-2 and variants in mouse models.…”
Section: Neutrophils (Nes)-based Strategiesmentioning
confidence: 85%
See 2 more Smart Citations
“…As adjuvants, the STING agonist CF501 was combined with human IgG Fc-conjugated receptor binding domain (RBD) from the original SARS-CoV-2 strain, inducing highly potent and durable protective immunity responses without apparent biological toxicity. 123,186 As mentioned earlier, Mn 2+ NPs can enhance retention and cellular uptake, leading to prolonged activation of the cGAS-STING pathway after injection. Zhang et al 187 found that NP manganese was the most potent adjuvant in stimulating immune responses to SARS-CoV-2 protein-based subunit vaccines, as evidenced by the concentration of RBD-specific IgG and specific neutralizing antibodies of SARS-CoV-2 and variants in mouse models.…”
Section: Neutrophils (Nes)-based Strategiesmentioning
confidence: 85%
“…121 Additionally, diABZI-4 has demonstrated efficacy in inhibiting virus replication in cells as a diABZI analogue. 122,123 Xie et al 117 explored enhancing the efficacy of the STING agonist by increasing diABZIs asymmetry. They incorporated a furan ring into benzimidazole to replace one benzimidazole moiety in diABZIs, creating a more asymmetric structure named HB3089.…”
Section: Nonnucleotide Small Molecule Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel with this, a recent study corroborated that the cGAS-STING pathway is a leading cause of aberrant IFN-I-induced immune responses in COVID-19, via mitochondrial DNA release in the endothelial cells, while pharmacological blocking of the STING pathway significantly reduced inflammatory status, particularly in the respiratory system [ 71 ]. Others advocate that designing STING inhibitors, such as H-151and VS-X4, could serve as novel therapeutic options in the late phase of SARS-CoV-2-like infections to alleviate the hyper-inflammation, as a result of the persistent STING activation, particularly in severe or critically ill patients [ 71 , 75 , 76 ].…”
Section: Published Research and Data Interpretationsmentioning
confidence: 99%
“…The relationship between STING and SARS-CoV-2 is complex [ 213 ]. During the initial stages of COVID-19 infection, the virus effectively suppresses STING activation by directly binding viral accessory protein ORF3a to STING [ 214 ].…”
Section: Sting-related Diseasesmentioning
confidence: 99%